Functions of education inspection in Spain: descriptive-comparative analysis of its regulations - Martel Robaina, Alexis (Avances en Supervisión Educativa, 2022)
Section 151 of the Spanish Education Act “Ley Orgánica 2/2006, of 3 of May”, as amended by the Spanish Education Act “Ley Orgánica 3/2020, of 29 of December”, provides for the eight functions within the education inspection framework. For this study, those functions will comprise the essential aspects and the starting point of this research, so a comparison between the similarities and the differences existing in the Autonomous Communities of the Spanish State (hereinafter referred to as CCAA) and its Autonomous Cities of Ceuta and Melilla can be carried out. The analysis of those aspects may further identify potential administrative and operational implications. Therefore, this paper scrutinizes the education inspection regulations applicable in the 17 Autonomous Communities of Spain and its Autonomous Cities of Ceuta and Melilla. This study also includes a Likert-type assessment scale to determine the degree of performance of such essential aspects.
Keywords: Education inspection; inspection roles; autonomous communities; Spanish Education Act “Ley Orgánica 2/2006”; Spanish Education Act “Ley Orgánica 3/2020”; Likert scale